2023
DOI: 10.1039/d2re00387b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Monte Carlo residence time distributions and kinetics in view of extrusion-based polymer modification and recycling

Abstract: Reactive extrusion (REX) is an important processing technique for polymer modification and mechanical/chemical recycling. In the present work, for the first time, a stochastic coupled macro-micro scale modeling framework is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…15,[49][50][51] The kMC algorithm has been successfully applied, for instance for free radical polymerization (FRP), [52][53][54][55][56] reversible deactivation radical polymerization (RDRP), 57,58 including atom transfer radical polymerization (ATRP), [59][60][61][62] reversible addition-fragmentation chain transfer polymerization (RAFT), 4,63,64 and nitroxide mediated polymerization (NMP), 65,66 surface-initiated polymerization (SIP), 67 radical photopolymerization, 68,69 network polymer synthesis, 51,70,71 (radical) depolymerization, [72][73][74] and multi-compartment polymerization. [75][76][77] In general, kMC algorithms sample (reaction) events in (bio) chemical processes through three main steps: (i) the calculation of the probabilities of all these events at a given time, (ii) the sampling of the (reaction) event and its reactants or species involved, to be executed at a priorly sampled stochastic time step, and (iii) the updating of the state of the chemical system. 24 These three steps are executed in a loop until a specific exit condition is met, which is usually the depletion of a reagent or the reaching a user-specified reaction time, yield, or conversion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,[49][50][51] The kMC algorithm has been successfully applied, for instance for free radical polymerization (FRP), [52][53][54][55][56] reversible deactivation radical polymerization (RDRP), 57,58 including atom transfer radical polymerization (ATRP), [59][60][61][62] reversible addition-fragmentation chain transfer polymerization (RAFT), 4,63,64 and nitroxide mediated polymerization (NMP), 65,66 surface-initiated polymerization (SIP), 67 radical photopolymerization, 68,69 network polymer synthesis, 51,70,71 (radical) depolymerization, [72][73][74] and multi-compartment polymerization. [75][76][77] In general, kMC algorithms sample (reaction) events in (bio) chemical processes through three main steps: (i) the calculation of the probabilities of all these events at a given time, (ii) the sampling of the (reaction) event and its reactants or species involved, to be executed at a priorly sampled stochastic time step, and (iii) the updating of the state of the chemical system. 24 These three steps are executed in a loop until a specific exit condition is met, which is usually the depletion of a reagent or the reaching a user-specified reaction time, yield, or conversion.…”
Section: Introductionmentioning
confidence: 99%
“…15,49–51 The k MC algorithm has been successfully applied, for instance for free radical polymerization (FRP), 52–56 reversible deactivation radical polymerization (RDRP), 57,58 including atom transfer radical polymerization (ATRP), 59–62 reversible addition–fragmentation chain transfer polymerization (RAFT), 4,63,64 and nitroxide mediated polymerization (NMP), 65,66 surface-initiated polymerization (SIP), 67 radical photopolymerization, 68,69 network polymer synthesis, 51,70,71 (radical) depolymerization, 72–74 and multi-compartment polymerization. 75–77…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of an initiator, the double bond can undergo free radical polymerization. Recent research has shown that grafting with MAH can be optimized but is still inefficient. , MAH is less reactive due to its symmetrical structure and low electron density around the carbon–carbon double bond . Furthermore, it is easily sublimated at high temperatures and is corrosive and irritating.…”
Section: Introductionmentioning
confidence: 99%
“…[12,[29][30][31][47][48][49][50] In PRE, the kMC method has been successfully applied for both polymerization (e.g., homogeneous free radical, [11,15,[51][52][53] nitroxide mediated, [54][55][56] atom transfer radical polymerization, [57][58][59][60][61] and dispersed phase thus heterogeneous polymerization [62][63][64][65][66][67][68] ), polymer modification [27,69,70] as well as polymer recycling, both via chemical and mechanical means. [71][72][73][74] As opposed to conditional Monte Carlo, [75][76][77] which deals with a posteriori mimicking of chemical structures simplifying the natural flow of reaction kinetics, the kMC method is based on the stochastic simulation algorithm (SSA), as proposed in the seminal work of Gillespie for reactions between elemental species. [16,78] According to SSA, each considered chemical reaction between species is listed as a reaction channel, the time evolution is tracked by sampling a stochastic time step, and a reaction channel is selected based on its probability of occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12,29–31,47–50 ] In PRE, the k MC method has been successfully applied for both polymerization (e.g., homogeneous free radical, [ 11,15,51–53 ] nitroxide mediated, [ 54–56 ] atom transfer radical polymerization, [ 57–61 ] and dispersed phase thus heterogeneous polymerization [ 62–68 ] ), polymer modification [ 27,69,70 ] as well as polymer recycling, both via chemical and mechanical means. [ 71–74 ]…”
Section: Introductionmentioning
confidence: 99%